Identification of Combinatorial Drugs that Synergistically Kill both Eribulin-Sensitive and Eribulin-Insensitive Tumor Cells - Richard J Rickles; Junji Matsui; Ping Zhu; Yasuhiro Funahashi; Jill M Grenier; Janine Steiger; Nanding Zhao; Bruce A Littlefield; Kenichi Nomoto; Toshimitsu Uenaka (Global Journal of Cancer Therapy - Peertechz Publications, 2015)
Eribulin sensitivity was examined in a panel of twenty-five human cancer cell lines representing a variety of tumor types, with a preponderance of breast and lung cancer cell lines. As expected, the cell lines vary in sensitivity to eribulin at clinically relevant concentrations. To identify combination drugs capable of increasing anticancer effects in patients already responsive to eribulin, as well as inducing de novo anticancer effects in non-responders, we performed a combinatorial high throughput screen to identify drugs that combine with eribulin to selectively kill tumor cells. Among other observations, we found that inhibitors of ErbB1/ErbB2 (lapatinib, BIBW-2992, erlotinib), MEK (E6201, trametinib), PI3K (BKM-120), mTOR (AZD 8055, everolimus), PI3K/mTOR (BEZ 235), and a BCL2 family antagonist (ABT-263) show combinatorial activity with eribulin. In addition, antagonistic pairings with other agents, such as a topoisomerase I inhibitor (topotecan hydrochloride), an HSP-90 inhibitor (17-DMAG), and gemcitabine and cytarabine, were identified. In summary, the preclinical studies described here have identified several combination drugs that have the potential to either augment or antagonize eribulin's anticancer activity. Further elucidation of the mechanisms responsible for such interactions may be important for identifying valuable therapeutic partners for eribulin.